Exploring the Effects of MXene on Nonisothermal Crystallization and Melting Behavior of β-Nucleated Isotactic Polypropylene - Wanxin Peng (MDPI AG, 2021)
In this study, one of the commonly used MXene (Ti3C2Tx) and β nucleated isotactic polypropylene (β-iPP)/MXene composites of different compositions were fabricated. The effects of MXene on non-isothermal crystallization and polymorphic behavior of β-iPP/MXene composites were comparatively studied. The non-isothermal crystallization kinetics indicates that for all samples, the lower cooling rates promote composites to crystallize at higher temperatures. When MXene and β-Nucleating agent (β-NA) are added separately, the crystallization temperature of composites shifts towards higher temperatures at all cooling rates. When MXene and β-NA are added simultaneously, the composite shows different cooling rate dependence, and the effects of improving crystallization temperatures is more obvious under rapid cooling. The activation energy of four samples iPP, iPP/MXene, iPP/β-NA, and iPP/MXene/β-NA were −167.5, −185.5, −233.8, and −218.1 kJ/mol respectively, which agree with the variation tendency of crystallization temperatures. The polymorphic behavior analysis obtained from Differential Scanning calorimetry (DSC) is affected by two factors: the ability to form β-crystals and the thermal stability of β-crystals. Because β-crystals tend to recrystallize to α-crystals below a critical temperature, to eliminate the effect of β-α recrystallization, the melting curves at end temperatures Tend = 50 °C and Tend = 100 °C are comparatively studied. The results show that more thermally unstable β-crystals would participate in β-α recrystallization with higher cooling rates. Moreover, thermal stability of β-crystals is improved by adding MXene. To further verify these findings, samples of three different thermal conditions were synthesized and analyzed by DSC, X-Ray Diffraction (XRD), and Polarized Light Optical Microscopy (PLOM), and the results were consistent with the above findings. New understandings of synthesizing β-iPP/MXene composites with adjustable morphologies and polymorphic behavior were proposed.